Thermal insulation wall repairing material and preparation method thereof

Through the combination and treatment of modified overfired magnesium oxide and other components, the existing insulation wall repair materials have been solved, and high bonding and good bonding are achieved. The effect of operability and high flowability extends the life of the restoration material and enhances the structural performance of the wall.

CN119462062AActive Publication Date: 2025-02-18WUHAN UNIV OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411554358.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing insulation wall repair materials have poor fluidity, short operating time, poor bonding and short life, which leads to problems such as cracking and aging and falling off of the wall.

Method used

采用改性过烧氧化镁、磷酸二氢铵、粉煤灰漂珠、水玻璃、钢渣粉、铝粉、α-半水石膏和黄原胶等组分,通过羟基化反应和表面活性剂改性处理,延长凝结时间,提高粘结性和流动性,并通过发泡剂增强结构性能。

Benefits of technology

It achieves high adhesion, good operability and high flowability, extends the service life of the restoration material, and enhances the structural performance and insulation effect of the wall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a thermal insulation wall repairing material and a preparation method thereof. The thermal insulation wall repair material provided by the invention is prepared from the following components in parts by weight: 125 to 166 parts of modified overburnt magnesium oxide, 120 to 165 parts of ammonium dihydrogen phosphate, 72 to 105 parts of fly ash floating beads, 20 to 55 parts of water glass, 25 to 55 parts of steel slag powder, 18 to 40 parts of aluminum powder, 10 to 40 parts of alpha-semi-hydrated gypsum, 15 to 45 parts of xanthan gum and 185 to 286 parts of water. According to the invention, a surface modification technology, a polymer enhancement technology and the like are fused, so that the modified magnesium oxide particles have good fluidity and controllable coagulation time in a later hydration process, and the adhesive property of the material can be improved in the later stage; after the modified overburnt magnesium oxide is fully mixed with the ammonium dihydrogen phosphate, the mixed mineral admixture, the water glass and the foaming agent, the prepared thermal insulation wall repairing material has high permeability, high fluidity, high cohesiveness and operability, and meanwhile, the service life of a thermal insulation wall is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation wall repair, and in particular to a thermal insulation wall repair material and a preparation method thereof. Background Art

[0002] As an important building energy-saving technology, exterior wall insulation technology has developed rapidly in China in the past 20 years. However, due to the complexity of exterior wall insulation engineering technology, the materials are more susceptible to aging under the climate of dry-wet alternation and freeze-thaw cycles, resulting in a series of quality problems such as hollowing, falling off, cracking, and water leakage, which have affected the safety and comfort of the living environment.

[0003] To solve this problem, my country has successively compiled standards such as "Standards for Repair of External Insulation Systems of Building Exterior Walls" (JGJ 376-2015) and "Technical Code for Renovation of External Insulation of Existing External Walls" (TCECS 574-2019), which provide guarantees for the standardized operation of relevant technologies. In general, when a small amount of hollowing and other phenomena occur in the early stage of the external insulation wall, the main method of repair is to inject adhesive materials into the cavity between the wall and the insulation layer by grouting. As a key link of this technology, the repair material has been studied to a certain extent. The repair materials used are mainly divided into organic repair materials and inorganic repair materials; organic repair materials include epoxy resin and polyurea, but epoxy resin is not resistant to acid and alkali corrosion and has average solvent resistance. When epoxy resin contacts the external insulation board of the insulation wall, it will cause hollowing problems in the wall due to similar solubility; inorganic repair materials mainly include various cement mortars, which have good durability, but their bonding strength with the wall interface is low, shrinkage is large, and permeability is poor, which makes it difficult to meet the strength requirements of wall repair.

[0004] Phosphate cement has excellent freeze-thaw resistance, heat resistance, good biocompatibility and other characteristics. It has good interfacial bonding performance with old concrete. It is often used as an interfacial repair material in engineering to repair damaged insulation walls, highway bridges and airport runways. It is an economical and efficient new repair material. However, due to the high initial viscosity and short reaction time of phosphate cement itself, it is difficult to construct in actual engineering applications, and it is difficult to fill the cavity of the insulation structure and cannot achieve effective bonding. To solve this problem, starting from the source of phosphate cement viscosity, there are currently studies on methods to improve its workability through a slow-release effect. For example, some scholars have proposed that microcapsules can be made by using a CaCO3 capsule wall material with a thickness of 30μm-80μm and magnesium oxide. When used, magnesium oxide is gradually released, thereby effectively delaying its coagulation. However, when preparing microcapsules in this way, it is difficult to control the capsule wall thickness, and the capsule wall material only plays a buffering role in later use, and has no other functions.

[0005] Therefore, there is an urgent need to develop a thermal insulation wall repair material with multiple functions such as high permeability, high adhesion, high fluidity, micro expansion, and long life. Summary of the invention

[0006] In view of this, the present invention aims to provide an insulation wall repair material to solve the problems of poor fluidity, short operability time, poor adhesion, short life, etc. of existing insulation wall repair materials, which in turn lead to the existing insulation walls being prone to cracking and aging and falling off.

[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0008] A thermal insulation wall repair material comprises the following components, measured by weight: 125-166 parts of modified overburned magnesium oxide, 120-165 parts of ammonium dihydrogen phosphate, 72-105 parts of fly ash floating beads, 20-55 parts of water glass, 25-55 parts of steel slag powder, 18-40 parts of aluminum powder, 10-40 parts of alpha-semihydrate gypsum, 15-45 parts of xanthan gum, and 185-286 parts of water.

[0009] Optionally, the modified overburned magnesium oxide is prepared by the following method:

[0010] Calcining magnesium oxide at high temperature to obtain overburned magnesium oxide;

[0011] By weight, 125 to 166 parts of the overburned magnesium oxide are ball-milled and added to 60 to 85 parts of anhydrous ethanol, and stirred until completely mixed, and then subjected to a hydroxylation reaction at a certain temperature. After the hydroxylation reaction is completed, the overburned magnesium oxide particles are filtered to obtain hydroxylated treated particles;

[0012] The hydroxylated overburned magnesium oxide particles are mixed with 10 to 35 parts of polyethylene glycol octylphenyl ether and stirred evenly, and then filtered and dried to obtain modified overburned magnesium oxide.

[0013] Optionally, the calcination temperature of the high-temperature calcination is 1600-1750° C., and the calcination time is 2.5-4.0 hours; and the particle size of the overburned magnesium oxide after ball milling is 20-30 μm.

[0014] Optionally, the reaction temperature of the hydroxylation reaction is 45-60° C., and the reaction time is 5-8 h.

[0015] Optionally, the mass ratio of the anhydrous ethanol to the polyethylene glycol octylphenyl ether is 2 to 6:1.

[0016] Optionally, the fly ash floating beads have a sphericity of 0.93 to 0.98 and a bulk density of 0.32 to 0.37 g / m 3, moisture content ≤0.5%; in terms of mass percentage, the particle size composition of the fly ash floating beads is: 10-40μm: 15%, 40-70μm: 40%, 70-100μm: 45%.

[0017] Optionally, the purity of NH4H2PO4 in the diammonium phosphate is ≥99%; the fineness of the steel slag powder is 100-150 mesh, the CaO content is 8.5%-10%, and the MgO content is 10%-12%.

[0018] Optionally, the water glass is one or more of sodium water glass and potassium water glass, and the SiO2 content is 26% to 30%, and the solid content is ≥40%.

[0019] Optionally, the effective content of the aluminum powder is ≥60%, and the particle size is ≤5μm; the final setting time of the α-hemihydrate gypsum is ≤30min, and the 2h flexural strength is ≥3.0MPa; the bulk density of the xanthan gum is 0.4-0.6g / mL, and the pH of the 1% xanthan gum solution is 6-8.

[0020] The second object of the present invention is to provide a method for preparing the above-mentioned thermal insulation wall repair material, the preparation method comprising the following steps:

[0021] 1) fully mixing the fly ash floating beads, the steel slag powder, the α-hemihydrate gypsum, and the modified overburned magnesium oxide to obtain a mixed powder A;

[0022] 2) dissolving the water glass in part of the water, wherein the ratio of the water glass to part of the water is 0.5-0.8, to obtain solution B;

[0023] 3) placing the mixed powder A in a stirring pot, adding the solution B, stirring rapidly for 30 to 55 seconds, adding the remaining water and the diammonium phosphate, stirring slowly for 20 to 50 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0024] 4) adding the aluminum powder and the xanthan gum into the magnesium ammonium phosphate cement mortar and foaming the mortar to obtain a thermal insulation wall repair material.

[0025] Compared with the prior art, the thermal insulation wall repair material of the present invention has the following advantages:

[0026] 1. The thermal insulation wall repair material of the present invention has high bonding properties. Based on the existing magnesium ammonium phosphate cementitious material having certain bonding properties, the present invention adds water glass, which effectively improves the morphology and structure of cement hydration products, making magnesium ammonium phosphate cement have better bonding properties. The main substance in water glass is silicate, and SiO3 in the solution 2-Mainly long-chain structures, these long-chain structures can be arranged in a spiral and form a cavity structure. The formed cavity structure has the ability to absorb the surrounding solvents and cations. With the increase in the amount of water glass, the concentration of SiO32- in the solution increases. More SiO32- long-chain structures will participate in the spiral arrangement process, which will increase the number of cavity structures and increase their size. Larger cavity structures can absorb more solvents and cations, which enhances the intermolecular interactions in the slurry system. At the same time, the intermolecular forces between the molecules in the slurry system and the surface of the old concrete also increase, which manifests as strong bonding. However, the addition of excessive water glass promotes the activation of fly ash, resulting in a shortened setting time of the slurry. At the same time, the addition of water glass will cause Mg in the slurry. 2+ Increase, increase the pH value of the solution, and then accelerate the coagulation speed of the slurry. For this reason, the present application modifies the surface of magnesium oxide by ethanol and polyethylene glycol octylphenyl ether, so that it wraps part of the magnesium oxide particles in cement hydration, thereby delaying its reaction with ammonium dihydrogen phosphate and water, and then prolonging its coagulation time. At the same time, the present invention adds a foaming agent aluminum powder and a foam stabilizer xanthan gum, so that the magnesium ammonium phosphate cement mortar can form a fine bubble structure, which can provide an additional insulation layer, enhance the structural performance of the wall, and improve the energy efficiency of the building. In the later stage of the reaction, the aluminum in the aluminum powder can react with the calcium-magnesium substance in α-hemihydrate gypsum and steel slag to generate expansive calcium aluminate, which complements the gas expansion and enhances the bonding strength with the wall interface.

[0027] 2. The thermal insulation wall repair material of the present invention has good operability. On the basis of ensuring the original bonding performance of magnesium ammonium phosphate cement, the setting time is significantly extended. In daily operation and construction, traditional retarders such as borax, boric acid and sodium tripolyphosphate are widely used. However, in the magnesium ammonium phosphate cement system, the boron-containing retarder will form a borophosphate magnesium phase during the hydration process. This mineral phase will wrap MgO, causing the excess retarder in the system to lose its effectiveness. The present invention uses anhydrous ethanol to introduce hydroxyl groups on the surface of magnesium oxide particles, and uses a surfactant polyethylene glycol octyl phenyl ether to modify the magnesium oxide particles. The modification principle is that polyethylene glycol octyl phenyl ether acts on the hydroxyl groups on the surface of magnesium oxide particles and adsorbs on the surface of the particles, wraps the magnesium oxide particles during the cement hydration process, delays the release time of the magnesium oxide particles, and thus plays a retarding role, improving the problem that the construction operability of magnesium ammonium phosphate cement is poor due to the too fast setting time. The present invention achieves the purpose of regulating the setting time of magnesium ammonium phosphate cement under the premise of using water glass. The polyethylene glycol octylphenyl ether used in the present invention is a nonionic surfactant with stable chemical properties and good compatibility with anhydrous ethanol. It is not easy to decompose and deteriorate, and can maintain good stability in acidic and alkaline environments.

[0028] 3. The thermal insulation wall repair material of the present invention has high fluidity. The present invention uses fly ash floating beads as a mineral admixture to replace part of magnesium oxide, thereby improving the fluidity of cement paste. The main hydration product of magnesium ammonium phosphate cement is NH4MgPO4·6H2O (i.e. struvite). Struvite crystals are usually relatively stable and can provide a higher cementing effect for the system. This is also the reason why magnesium ammonium phosphate cement itself has greater bonding properties. However, high viscosity is not conducive to construction and it is not easy to make the cement paste flow quickly. Therefore, adding fly ash floating beads to magnesium ammonium phosphate cement, on the one hand, reduces the total porosity of magnesium ammonium phosphate cement, increases the density of the matrix, and hinders the penetration of water molecules into the matrix; on the other hand, due to the smooth surface of fly ash floating beads, the friction resistance in magnesium phosphate cement can be reduced, making the cement paste easier to flow. The surface of magnesium oxide particles is modified at the molecular level using a non-ionic surfactant. In the later stage of the reaction, polyethylene glycol octylphenyl ether can work together with fly ash floating beads to enhance the fluidity of the slurry and improve construction efficiency. Compared with general mineral admixtures, fly ash beads can more effectively improve the fluidity of the slurry and can be quickly squeezed out during the actual construction process, thereby improving construction efficiency. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.

[0030] The performance indicators of the raw materials used in Examples 1-6 of the present invention are as follows:

[0031] The sphericity of fly ash beads is 0.96 and the bulk density is 0.35g / m 3 , moisture content is 0.4%; in terms of mass percentage, the particle size composition of the fly ash floating beads is: 10-40μm: 15%, 40-70μm: 40%, 70-100μm: 45%.

[0032] The purity of NH4H2PO4 in diammonium phosphate is ≥99%;

[0033] The fineness of the steel slag powder is 150 mesh, the CaO content is 9.0%, and the MgO content is 11.5%;

[0034] The SiO2 content in sodium water glass and potassium water glass is 30%, and the solid content is ≥40%;

[0035] The effective content of aluminum powder is 70% and the particle size is 3-5μm;

[0036] The final setting time of α-hemihydrate gypsum is 28min, and the 2h flexural strength is 3.68MPa

[0037] The bulk density of xanthan gum is 0.5 g / mL, and the pH of a 1% xanthan gum solution is 8.

[0038] Example 1

[0039] A thermal insulation wall repair material comprises the following components, measured by weight: 125 parts of modified overburned magnesium oxide, 120 parts of ammonium dihydrogen phosphate, 72 parts of fly ash floating beads, 20 parts of sodium water glass, 25 parts of steel slag powder, 18 parts of aluminum powder, 10 parts of alpha-hemihydrate gypsum, 15 parts of xanthan gum, and 185 parts of water.

[0040] Among them, modified overburned magnesium oxide is prepared by the following method:

[0041] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0042] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm;

[0043] 125 parts by weight of overburned magnesium oxide particles were added to 60 parts of anhydrous ethanol and stirred for 10 minutes until completely mixed, and then a hydroxylation reaction was carried out at 50° C. to introduce hydroxyl groups on the surface of the overburned magnesium oxide particles. After the hydroxylation reaction lasted for 5 hours, the overburned magnesium oxide particles were filtered to obtain hydroxylated overburned magnesium oxide particles;

[0044] The hydroxylated overburned magnesium oxide particles were mixed with 10 parts of polyethylene glycol octylphenyl ether and stirred for 15 minutes until the mixture was uniform, and then filtered and dried to obtain modified overburned magnesium oxide.

[0045] The above-mentioned thermal insulation wall repair material is specifically prepared by the following method:

[0046] 1) 72 parts of fly ash floating beads, 25 parts of steel slag powder, 10 parts of α-hemihydrate gypsum, and 125 parts of modified overburned magnesium oxide were fully mixed to obtain a mixed powder A;

[0047] 2) Weigh 20 parts of sodium water glass and 33 parts of water (the ratio of water glass to water is 0.6), add the water glass into the water and stir thoroughly until it is completely dissolved to obtain solution B;

[0048] 3) placing the mixed powder A in a stirring pot, adding solution B, stirring rapidly for 30 seconds, adding 152 parts of water and 120 parts of diammonium phosphate, stirring slowly for 20 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0049] 4) 18 parts of aluminum powder and 15 parts of xanthan gum are added to magnesium ammonium phosphate cement mortar and foamed to obtain a thermal insulation wall repair material.

[0050] Example 2

[0051] A thermal insulation wall repair material comprises the following components, measured by weight: 137 parts of modified overburned magnesium oxide, 131 parts of ammonium dihydrogen phosphate, 80 parts of fly ash floating beads, 28 parts of sodium water glass, 32 parts of steel slag powder, 24 parts of aluminum powder, 20 parts of alpha-hemihydrate gypsum, 23 parts of xanthan gum, and 212 parts of water.

[0052] Among them, modified overburned magnesium oxide is prepared by the following method:

[0053] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0054] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm;

[0055] 137 parts by weight of overburned magnesium oxide particles were added to 67 parts of anhydrous ethanol and stirred for 10 minutes until completely mixed, and then a hydroxylation reaction was carried out at 50° C. to introduce hydroxyl groups on the surface of the overburned magnesium oxide particles. After the hydroxylation reaction lasted for 5 hours, the overburned magnesium oxide particles were filtered to obtain hydroxylated overburned magnesium oxide particles;

[0056] The hydroxylated overburned magnesium oxide particles were mixed with 18 parts of polyethylene glycol octylphenyl ether and stirred for 15 minutes until the mixture was uniform, and then filtered and dried to obtain modified overburned magnesium oxide.

[0057] The above-mentioned thermal insulation wall repair material is specifically prepared by the following method:

[0058] 1) 80 parts of fly ash floating beads, 32 parts of steel slag powder, 20 parts of α-hemihydrate gypsum, and 137 parts of modified overburned magnesium oxide were fully mixed to obtain a mixed powder A;

[0059] 2) Weigh 28 parts of sodium water glass and 47 parts of water (the ratio of water glass to water is 0.6), add the water glass into the water and stir thoroughly until it is completely dissolved to obtain solution B;

[0060] 3) placing the mixed powder A in a stirring pot, adding solution B, stirring rapidly for 30 seconds, adding 165 parts of water and 131 parts of diammonium phosphate, stirring slowly for 20 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0061] 4) 24 parts of aluminum powder and 23 parts of xanthan gum are added to magnesium ammonium phosphate cement mortar and foamed to obtain a thermal insulation wall repair material.

[0062] Example 3

[0063] A thermal insulation wall repair material comprises the following components, measured by weight: 145 parts of modified overburned magnesium oxide, 143 parts of ammonium dihydrogen phosphate, 89 parts of fly ash floating beads, 36 parts of sodium water glass, 39 parts of steel slag powder, 30 parts of aluminum powder, 25 parts of α-hemihydrate gypsum, 30 parts of xanthan gum, and 236 parts of water.

[0064] Among them, modified overburned magnesium oxide is prepared by the following method:

[0065] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0066] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm;

[0067] 145 parts by weight of overburned magnesium oxide particles were added to 76 parts of anhydrous ethanol and stirred for 10 minutes until completely mixed, and then a hydroxylation reaction was carried out at 50° C. to introduce hydroxyl groups on the surface of the overburned magnesium oxide particles. After the hydroxylation reaction was carried out for 5 hours, the overburned magnesium oxide particles were filtered to obtain hydroxylated overburned magnesium oxide particles;

[0068] The hydroxylated overburned magnesium oxide particles were mixed with 25 parts of polyethylene glycol octylphenyl ether and stirred for 15 minutes until the mixture was uniform, and then filtered and dried to obtain modified overburned magnesium oxide.

[0069] The above-mentioned thermal insulation wall repair material is specifically prepared by the following method:

[0070] 1) 89 parts of fly ash floating beads, 39 parts of steel slag powder, 25 parts of α-hemihydrate gypsum, and 145 parts of modified overburned magnesium oxide were fully mixed to obtain a mixed powder A;

[0071] 2) Weigh 36 parts of sodium water glass and 60 parts of water (the ratio of water glass to water is 0.6), add the water glass into the water and stir thoroughly until it is completely dissolved to obtain solution B;

[0072] 3) placing the mixed powder A in a stirring pot, adding solution B, stirring rapidly for 30 seconds, adding 176 parts of water and 143 parts of diammonium phosphate, stirring slowly for 20 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0073] 4) 30 parts of aluminum powder and 30 parts of xanthan gum are added to magnesium ammonium phosphate cement mortar and foamed to obtain a thermal insulation wall repair material.

[0074] Example 4

[0075] A thermal insulation wall repair material comprises the following components, measured by weight: 155 parts of modified overburned magnesium oxide, 152 parts of ammonium dihydrogen phosphate, 90 parts of fly ash floating beads, 45 parts of sodium water glass, 44 parts of steel slag powder, 35 parts of aluminum powder, 36 parts of α-hemihydrate gypsum, 36 parts of xanthan gum, and 255 parts of water.

[0076] Among them, modified overburned magnesium oxide is prepared by the following method:

[0077] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0078] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm;

[0079] 155 parts by weight of overburned magnesium oxide particles were added to 80 parts of anhydrous ethanol and stirred for 10 minutes until completely mixed, and then a hydroxylation reaction was carried out at 50° C. to introduce hydroxyl groups on the surface of the overburned magnesium oxide particles. After the hydroxylation reaction was carried out for 5 hours, the overburned magnesium oxide particles were filtered to obtain hydroxylated treated particles;

[0080] The hydroxylated overburned magnesium oxide particles were mixed with 30 parts of polyethylene glycol octylphenyl ether and stirred for 15 minutes until the mixture was uniform, and then filtered and dried to obtain modified overburned magnesium oxide.

[0081] The above-mentioned thermal insulation wall repair material is specifically prepared by the following method:

[0082] 1) 90 parts of fly ash floating beads, 44 parts of steel slag powder, 36 parts of α-hemihydrate gypsum, and 155 parts of modified overburned magnesium oxide were fully mixed to obtain a mixed powder A;

[0083] 2) Weigh 45 parts of sodium water glass and 75 parts of water (the ratio of water glass to water is 0.6), add the water glass into the water and stir thoroughly until it is completely dissolved to obtain solution B;

[0084] 3) placing the mixed powder A in a stirring pot, adding solution B, stirring rapidly for 30 seconds, adding 180 parts of water and 152 parts of diammonium phosphate, stirring slowly for 20 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0085] 4) 35 parts of aluminum powder and 36 parts of xanthan gum are added to magnesium ammonium phosphate cement mortar and foamed to obtain a thermal insulation wall repair material.

[0086] Example 5

[0087] A thermal insulation wall repair material comprises the following components, measured by weight: 166 parts of modified overburned magnesium oxide, 165 parts of ammonium dihydrogen phosphate, 105 parts of fly ash beads, 55 parts of sodium water glass, 55 parts of steel slag powder, 40 parts of aluminum powder, 40 parts of alpha hemihydrate gypsum, 45 parts of xanthan gum, and 286 parts of water.

[0088] Among them, modified overburned magnesium oxide is prepared by the following method:

[0089] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0090] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm;

[0091] 166 parts by weight of overburned magnesium oxide particles were added to 85 parts of anhydrous ethanol and stirred for 10 minutes until completely mixed, and then a hydroxylation reaction was carried out at 50° C. to introduce hydroxyl groups on the surface of the overburned magnesium oxide particles. After the hydroxylation reaction lasted for 5 hours, the overburned magnesium oxide particles were filtered to obtain hydroxylated overburned magnesium oxide particles;

[0092] The hydroxylated overburned magnesium oxide particles were mixed with 35 parts of polyethylene glycol octylphenyl ether and stirred for 15 minutes until the mixture was uniform, and then filtered and dried to obtain modified overburned magnesium oxide.

[0093] The above-mentioned thermal insulation wall repair material is specifically prepared by the following method:

[0094] 1) 105 parts of fly ash floating beads, 55 parts of steel slag powder, 40 parts of α-hemihydrate gypsum, and 166 parts of modified overburned magnesium oxide were fully mixed to obtain a mixed powder A;

[0095] 2) Weigh 55 parts of sodium water glass and 92 parts of water (the ratio of water glass to water is 0.6), add the water glass into the water and stir thoroughly until it is completely dissolved to obtain solution B;

[0096] 3) placing the mixed powder A in a stirring pot, adding solution B, stirring rapidly for 30 seconds, adding 194 parts of water and 165 parts of diammonium phosphate, stirring slowly for 20 seconds, and obtaining magnesium ammonium phosphate cement mortar;

[0097] 4) adding 40 parts of aluminum powder and 45 parts of xanthan gum into magnesium ammonium phosphate cement mortar and foaming the mortar to obtain a thermal insulation wall repair material.

[0098] Example 6

[0099] The difference between this embodiment and embodiment 1 is that the water glass is a mixture of sodium water glass and potassium water glass in a mass ratio of 1:1, and the rest is the same as embodiment 1.

[0100] Comparative Example 1

[0101] The difference between this comparative example and Example 1 is that in this comparative example, anhydrous ethanol and polyethylene glycol octylphenyl ether are not used to perform surface modification treatment on the magnesium oxide particles.

[0102] That is, the modified overburned magnesium oxide of this comparative example is prepared by the following method:

[0103] The magnesium oxide is calcined at high temperature to obtain overburned magnesium oxide. Under the action of high temperature, the grain size and particle density of MgO increase significantly, which can significantly reduce the activity of magnesium oxide.

[0104] The overburned magnesium oxide is placed in a ball mill for mechanical grinding and then sieved to obtain overburned magnesium oxide particles with a particle size of 20 to 30 μm.

[0105] Comparative Example 2

[0106] The difference between this comparative example and Example 1 is that water glass is not used in the preparation of magnesium ammonium phosphate cement mortar in this comparative example.

[0107] Comparative Example 3

[0108] The difference between this comparative example and Example 1 is that this comparative example does not use α-hemihydrate gypsum. In order to ensure that the proportions of other components remain unchanged, 10 parts of α-hemihydrate gypsum are replaced by 10 parts of steel slag powder.

[0109] The test methods for the tensile bond strength, shear strength, fluidity and setting time of the thermal insulation wall repair materials of Examples 1-6 and Comparative Examples 1-3 prepared according to the above technical scheme are as follows:

[0110] The tensile bond strength is tested with reference to JGJ144-2019 "Technical Standard for External Wall Insulation Engineering"; the shear strength is tested with reference to GB / T 7124-2008 "Determination of Tensile Shear Strength of Adhesives (Rigid Material to Rigid Material)"; the fluidity is tested with reference to GB / T 2419-2005 "Cement Mortar Fluidity Test Standard"; the setting time is tested with reference to GB / T1346-2011 "Cement Standard Consistency Water Consumption, Setting Time, Stability Test Method".

[0111] Tensile bond strength: Apply the prepared insulation wall repair material slurry to an insulation board or concrete wall with a thickness of 45 mm with a coating thickness of 8 mm. Then install the sample on a tensile testing machine with a tensile speed of 0.1 mm / min and record the tensile force when stretched to failure.

[0112] Shear strength: Put the prepared thermal insulation wall repair material slurry into the connecting hole formed by the upper tie rod and the lower tie rod of the shear device, measure the thickness and width of the shear load part in the middle of the sample, start the motor, shear the sample, and record its maximum shear force value. The shear device is composed of two steel tie rods (upper tie rod and lower tie rod), the working part width of the upper tie rod is 30mm, and the working parts on both sides of the lower tie rod are 25mm wide.

[0113] Fluidity: Place the truncated cone mold in the center of the table top, then slowly pour the prepared thermal insulation wall repair material slurry into the truncated cone mold, tamp it with a tamping rod and quickly lift it up. After waiting for 1 minute, use a caliper to measure the diameters of the two directions perpendicular to each other on the bottom of the slurry, calculate the average value, take the integer, and the unit is mm. The average value is the fluidity of the cement slurry. The dimensions of the truncated cone mold are: height 60mm, upper inner diameter 70mm, lower inner diameter 100mm.

[0114] Setting time: slowly pour the prepared insulation wall repair material slurry into the test mold, put the test mold under the test needle, tighten the screws and suddenly loosen them, and observe the pointer reading when the test needle stops sinking. Measure once every 3 minutes, and express the setting time of cement slurry in minutes. The specification of the test mold is a truncated cone with a depth of 40mm±0.2mm, a bottom inner diameter of Φ65mm±0.5mm, and a bottom inner diameter of Φ75mm±0.5mm. Each test mold should be equipped with a flat glass with a side length or diameter of about 100mm and a thickness of 4-5mm.

[0115] The main performance indicators of the thermal insulation wall repair materials prepared in Examples 1-6 and Comparative Examples 1-3 are tested according to the above performance testing method and are shown in Table 1.

[0116] It can be seen from the experimental results of Example 1 and Comparative Example 1 in Table 1 that the failure to perform molecular-level modification on the surface of magnesium oxide particles will accelerate the setting time of cement paste, while the use of anhydrous ethanol to perform surface hydroxylation treatment on magnesium oxide particles and the use of polyethylene glycol octyl phenyl ether to perform molecular-level modification on the surface of magnesium oxide particles delays the setting time of cement. The reason is that magnesium oxide particles are wrapped by polyethylene glycol octyl phenyl ether, which inhibits the release of magnesium oxide particles in the early stage of hydration of magnesium ammonium phosphate cement, thereby delaying the hydration process of cement, thereby delaying the setting time of cement and providing convenience for the actual construction process.

[0117] From the experimental results of Example 1 and Comparative Example 2 in Table 1, it can be seen that when water glass is not added, the setting time of the cement paste is longer, but its fluidity is somewhat reduced compared with Example 2. This is because the main substance in water glass is sodium silicate, and the SiO3 in the solution 2-Mainly long chain structures, these long chain structures can be arranged in spirals and form cavity structures, which have the ability to absorb surrounding solvents and cations. With the increase of water glass content, these cavity structures become larger, and larger cavity structures can absorb more solvents and cations, which enhances the intermolecular interaction in the slurry system. At the same time, the intermolecular force between the molecules in the slurry system and the surface of the old concrete also increases, thereby increasing the initial viscosity of the slurry.

[0118] It can be seen from the experimental results of Example 1 and Example 6 in Table 1 that the bonding strength of the cement paste is greater when two kinds of water glasses are added at the same time. The reason is that after the addition of potassium water glass, it will react with ammonium dihydrogen phosphate to precipitate colloidal potassium silicate, which will provide greater bonding performance for the slurry and increase the bonding strength between the wall and the repair material.

[0119] It can be seen from the experimental results of Example 1 and Comparative Example 3 in Table 1 that when α-hemihydrate gypsum is not added, the bonding strength of the cement paste will decrease. The reason is that in the later stage of the reaction, the aluminum in the foaming agent aluminum powder can react with the calcium and magnesium substances in α-hemihydrate gypsum and steel slag to generate expansive ettringite, which complements the gas expansion and enhances the bonding strength with the wall interface.

[0120] Table 1

[0121]

[0122] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermal insulation wall repair material, characterized in that: The invention comprises the following components by weight: 125-166 parts of modified overburned magnesium oxide, 120-165 parts of ammonium dihydrogen phosphate, 72-105 parts of fly ash floating beads, 20-55 parts of water glass, 25-55 parts of steel slag powder, 18-40 parts of aluminum powder, 10-40 parts of α-semihydrate gypsum, 15-45 parts of xanthan gum and 185-286 parts of water.

2. The thermal insulation wall repair material according to claim 1, characterized in that: The modified overburned magnesium oxide is prepared by the following method: Calcining magnesium oxide at high temperature to obtain overburned magnesium oxide; By weight, 125 to 166 parts of the overburned magnesium oxide are ball-milled and added to 60 to 85 parts of anhydrous ethanol, and stirred until completely mixed, and then subjected to a hydroxylation reaction at a certain temperature. After the hydroxylation reaction is completed, the overburned magnesium oxide particles are filtered to obtain hydroxylated overburned magnesium oxide particles; The hydroxylated overburned magnesium oxide particles are mixed with 10 to 35 parts of polyethylene glycol octylphenyl ether and stirred evenly, and then filtered and dried to obtain modified overburned magnesium oxide.

3. The thermal insulation wall repair material according to claim 2, characterized in that: The calcination temperature of the high-temperature calcination is 1600-1750° C., and the calcination time is 2.5-4.0 hours; the particle size of the overburned magnesium oxide after ball milling is 20-30 μm.

4. The thermal insulation wall repair material according to claim 2, characterized in that: The reaction temperature of the hydroxylation reaction is 45-60° C., and the reaction time is 5-8 hours.

5. The thermal insulation wall repair material according to claim 2, characterized in that: The mass ratio of the anhydrous ethanol to the polyethylene glycol octylphenyl ether is 2 to 6:

1.

6. The thermal insulation wall repair material according to claim 1, characterized in that: The fly ash floating beads have a sphericity of 0.93-0.98 and a bulk density of 0.32-0.37 g / m 3 , moisture content ≤0.5%; in terms of mass percentage, the particle size composition of the fly ash floating beads is: 10-40μm: 15%, 40-70μm: 40%, 70-100μm: 45%.

7. The thermal insulation wall repair material according to claim 1, characterized in that: The purity of NH4H2PO4 in the diammonium phosphate is ≥99%; the fineness of the steel slag powder is 100-150 meshes, the CaO content is 8.5%-10%, and the MgO content is 10%-12%.

8. The thermal insulation wall repair material according to claim 1, characterized in that: The water glass is one or more of sodium water glass and potassium water glass, and the SiO2 content is 26% to 30%, and the solid content is ≥40%.

9. The thermal insulation wall repair material according to claim 1, characterized in that: The effective content of the aluminum powder is ≥60%, and the particle size is ≤5μm; the final setting time of the α-hemihydrate gypsum is ≤30min, and the 2h flexural strength is ≥3.0MPa; the bulk density of the xanthan gum is 0.4-0.6g / mL, and the pH of the 1% xanthan gum solution is 6-8.

10. A method for preparing the thermal insulation wall repair material according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) fully mixing the fly ash floating beads, the steel slag powder, the α-hemihydrate gypsum, and the modified overburned magnesium oxide to obtain a mixed powder A; 2) dissolving the water glass in part of the water, wherein the ratio of the water glass to part of the water is 0.5-0.8, to obtain solution B; 3) placing the mixed powder A in a stirring pot, adding the solution B, stirring rapidly for 30 to 55 seconds, adding the remaining water and the diammonium phosphate, stirring slowly for 20 to 50 seconds, and obtaining magnesium ammonium phosphate cement mortar; 4) adding the aluminum powder and the xanthan gum into the magnesium ammonium phosphate cement mortar and foaming the mortar to obtain a thermal insulation wall repair material.

Citation Information

Patent Citations

  • Phosphate cellular concrete and process for producing its product

    CN101492280A

  • Foamed magnesium phosphate cement material

    CN104496532A

  • Foam concrete material and preparation method thereof

    CN104744069A

  • Phosphate cement based patching material and preparation method thereof

    CN107056225A

  • High-molecular polymer modified magnesium oxide expanding agent, and preparation method and application thereof

    CN109721273A